2020
DOI: 10.1177/0020294020922264
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of fractional order internal model controller design on buck and boost converter

Abstract: In this paper, fractional order internal model control technique is formulated for non-ideal dc–dc buck and boost converter. The fractional order internal model control approach integrates the concept of Commande Robuste d’Ordre Non Entier principle for tuning a fractional order filter with internal model control scheme. The final controller can be expressed as a series combination of proportional integral derivative controller and a fractional order low pass filter. To assess the robustness of the proposed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Li et al 8 designed an adaptive sliding mode controller to compensate the input uncertainties for a class of fractional order nonlinear systems with unknown external disturbances and input uncertainties. Jain et al 9 proposed a fractional order internal model control method for non-ideal dc-dc buck and boost converter.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 8 designed an adaptive sliding mode controller to compensate the input uncertainties for a class of fractional order nonlinear systems with unknown external disturbances and input uncertainties. Jain et al 9 proposed a fractional order internal model control method for non-ideal dc-dc buck and boost converter.…”
Section: Introductionmentioning
confidence: 99%
“…3 Hence, complicated control schemes are needed to cope with non-modeled system/actuator dynamics and non-measurable disturbances; for example, fuzzy logic control, 8,9,10 feedback and feed-forward proportional integral derivative (PID) control, 11,12,13 and adaptive control. 14,15,16 Additional control schemes include active disturbance rejection control, 17,18,19 internal model control 20,21 and intelligent control. 22,23 However, the complexity of these solutions significantly increases the computational burden and makes them unsuitable for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Stability, robustness against parameter variations and acceptable performance indicators were the improvements. In (Jain et al, 2020) a fractional-order internal model controller was suggested. The control strategy is the combination of a PID controller and a non-integer order low pass filter.…”
Section: Introductionmentioning
confidence: 99%